Ground-state oxygen holes and the metal–insulator transition in the negative charge-transfer rare-earth nickelates - Valentina Bisogni (Nature Portfolio, 2016)
Rare-earth perovskite nickelates show intriguing metal–insulator transitions, whose mechanism remains elusive. Here, Bisogni et al. evidenced a 3d8 Ni configuration together with abundance of oxygen 2p holes in the ground state of a NdNiO3thin film, suggesting a negative charge-transfer scenario.